The Malay Historiography: A Study of Raja Ali Haji’s Tuhfat Al-Nafis - Alimuddin Hassan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The Tuhfat al-Nafs book is one of the historical works on Malay history to this day. This book was written by Raja Ali Haji in 1282 H on the 5th of Rabi'al-Akhir. According to Raja Ali Haji, this book was written when he obtained the book from Sayyid Al-Sharif ‘Abd Al-Rahman ibn Sayyid Al-Syarif Kasim Sultan of Pontianak ibn Sayyid Al-Syarif‘ Abd Al-Rahman Al-Kadri.